Active Methodologies: Tools for teacher empowerment (Docentes 2.0 Journal, 2019)
Nowadays, faced with the changes and complexity of this new era, learning and knowledge merit active methodologies to empower human talent to create meaningful experiences. In this sense, empowering teachers with these methodologies that invite them to experiment "(...) new ways of learning, communicating, assessing and connecting with reality" [1], that is, changes in their relationship with knowledge that, at the same time, promote educational trans-formations, doing it in an interactive and active way so that through experience, teachers and students have a constructive formation. Within these active methodologies are: case methods, question-based teaching, one-minute paper, peer-to-peer learning, illustration analysis, graphic organizers, analogies, expository classes, problem-based learning, role play, collaborative work, learning in the service, among others. This paper aims to analyze the role of active methodologies as tools for teacher empowerment in non-educating professionals through a documentary research on the subject under study, as active methodologies allow: improve communication, develop knowledge, skills and skills and finally the creation of positive environments for meaningful learning through play, technology, innovation, creativity and others.
Keywords: Active Methodologies; Teacher; Empowerment